Development of an outdoor lighting control system using expert system - EKREN, NAZMİ; ATİŞ, SELÇUK (ELSEVIER SCIENCE SA, 2016)
In this study, an intelligent energy-efficient outdoor lighting control system was developed that could be used in green buildings as well as intelligent building functions, and contribute to the reduction of carbon dioxide emissions by using more conservation of electric energy and daylight more efficiently. The intelligent energy-efficient lighting control system was based on expert system is one of the artificial intelligence techniques and has four functions running in real-time. The first function is controlling and monitoring of the lamp groups. The other functions are fault diagnosis in lambs and power lines connected to the lamp groups and the load estimation of lamp groups. The expert system was written in two separate computer and microcontroller based environments by using knowledge-based rules. The rule base of real-time control and monitoring function contains 213 rules. During the education semester operation mode which real-time control and monitoring function was implemented, an average of 33% conservation was achieved in energy consumption. The system is the first expert system application in which an expert system is used to control and monitor outdoor lighting as well as perform load estimate and fault diagnosis. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Outdoor lighting; Energy conservation; Expert system; ENERGY MANAGEMENT; BUILDINGS; SAVINGS